Analysis of children's everyday language experiences using longform audio: promises and pitfalls (Análisis de las experiencias lingüísticas cotidianas de niños y niñas utilizando audio de formato largo: posibles ventajas y dificultades). Issue 2 (3rd April 2021) - Soderstrom, Melanie
ABSTRACT: Emerging audio technologies over the last decade have provided a new, unprecedented window into the everyday lives of infants and young children. These new approaches will allow us to begin to address longstanding questions about the nature of language experiences across languages, communities and situations and the role of these experiences in language development across contexts. Here, I discuss the primary technology, LENA®, as well as more recent technological developments, and some of the recent findings in this domain. I also describe recent efforts to leverage these capabilities towards a much broader vision of exploring diverse child language experiences using largescale collaborative efforts.